The mycobiota associated with paper archives and their potential control - SAIFELDIN A.F. EL-NAGAREABI; ABDULKADIRI E. ELSHAFIE; UMAIMA A AL-HINAI (Smujo International, 2014)
El-Nagerabi SAF, Elshafie AE, Al-Hinai UA. 2014. The mycobiota associated with paper archives and their potential control. Nusantara Bioscience 6: 19-25. Historical collections kept in archives and libraries represent a cultural and artistic heritage of innumerable value. Recently in Oman, more than seventy thousand documents were collected from different countries and displayed as archives showed evident sign of mold contamination. The objectives of the present study were to screen these archives for mold invasion and a test for the effective control measure. For this, 102 samples were collected from documents of different sources and incubated on potato dextrose agar (PDA) at ambient temperature (25 â—‹CÂ±2). The isolated fungi were identified microscopically and confirmed with DNA extraction, PCR and DNA sequencing. Twenty-two fungal species belonging to 11 genera were recovered. The genus Penicillium (46.8%) was the most prevalent, followed by Aspergillus (30.7%), Cladosporium (7%), Rhizopus (4%), and Chaetomium (3.5%) whereas the remaining 6 genera represent only 8%. Eleven species were previously reported from similar substrates, whereas 11 species and one genus are new records for the mycoflora of archives. Sodium hypochlorite at 0.3-5.2% completely inhibited the fungal growth of the 10 tested fungal isolates with minimum inhibition concentration at 0.7%. Fumigation of books with 0.7-5.2% sodium hypochlorite completely inhibited all fungi without evident damage of the documents or ink discoloration. Therefore, sodium hypochlorite can be recommended as effective and eco-friendly disinfectant for archives comparable to other hazardous chemicals.